The Norman Sicilian court as a centre for the translation of Classical texts. Issue 2 (2nd July 2020) - Angold, Michael
Abstract : The translations into Latin from Greek and Arabic of works by Plato, Aristotle, Ptolemy, Diogenes Laertes, and others are very well known. They were mostly done at the Norman Sicilian court in the early years of William I's reign (1154–1166) and carried out by or under the supervision of Henry Aristippus, who was a royal official. Not much progress has been made over the question of the Norman Sicilian Translations since Charles Homer Haskins brought them to the attention of scholars over a century ago. The trouble is that they have mainly been treated as part of a translating movement, which swept the Latin West from the end of the eleventh century, which in some small way it was. But a better way of understanding their true significance is to examine them through the prism of Hubert Houben's notion of Norman Sicily as a "Third Space" between Byzantium, the Latin West and Islam. Then it becomes clear that they not only served to create an image of the Norman king, which set him apart from contemporary rulers, whether from the Latin West, Byzantium or Islam, but also contributed to the marked individuality of the culture of the Norman Sicilian court.